Linear Porokeratotic Adnexal Ostial Nevus with Dermoscopic Features - Sunanda Arun Mahajan; Yallappa Ramachandrappa Kabbannavar; Surender Singh (Wolters Kluwer Medknow Publications, 2022)
Porokeratotic adnexal ostial nevus is a rare nevoid condition, with a characteristic histological feature of coronoid lamella involving the acrosyringium and the hair follicle. Here we report a case of an 11-year-old female child presented with multiple hyperpigmented and hyperkeratotic papules present over the posterior aspect of right lower extremities along Blaschko's lines.